Zero Extension for the Dirichlet Problem of the Biharmonic Equation - Shaopeng Xu; Chong Yu (Mathematics)
In this paper, we consider whether the zero extension of a solution to the Dirichlet problem for the biharmonic equation in a smaller domain remains a solution to the corresponding extended problem in a larger domain. We analyze classical and strong solutions, and present a necessary and sufficient condition under each framework, respectively.